A Visualization of Ultrasonic Beam from a Medical Transducer using a Combination of Background-Oriented Schlieren Imaging with Hilbert Transformation - Sasono, Margi; Rusdiarna IP, Apik (Jurnal Ilmu Fisika, 2025)
Ultrasonics in the medical field require a safe treatment for patients. The uncontrolled intensities of the ultrasonic waves cause ineffective treatment. So far, the hydrophone probe provides a standard for ultrasonic visualization. However, this method has constraints such as being time-consuming, intrusive, and requiring off-axis measurements. In this paper, an optical method called background-oriented schlieren imaging (BOSI) has been developed as an alternative. The BOSI uses a background of fringe patterns captured by a digital camera. The ultrasonic waves in water displace the patterns relative to the reference. A Hilbert Transform (HT) has been used to estimate the displacement of patterns proportional to the phase difference. The developed BOSI reconstructs these phase differences as an ultrasonic visualization. This paper reports that the developed BOSI is capable of visualizing the ultrasonic waves produced by a 1-MHz frequency medical transducer operated in continuous-wave (CW) mode. The visualization shows an undulation of phase difference that corresponds to the change in water density due to ultrasonic exposure. Meanwhile, the amplitude mode is proportional to the ultrasonic intensity profile. Thus, the developed BOSI is promising to be used as a calibration device to ensure safe ultrasonics in the medical field.